Manajemen Risiko Kecelakaan Kerja Menggunakan Metode House of Risk Pada Proyek Pembangunan Apartemen Alessandro Citraland Vittorio - Ramadhani, Salits Laila (Jurnal Vokasi Teknik Sipil, 2023)
Construction projects are a sector that is growing very rapidly which are carried out in complex and difficult conditions, on the other hand industrial projects use human and machine power so that they have the potential to increase the risk of work accidents. Risks may have an impact on the productivity, performance, quality, cost of the project. It is said that risk is a result that may occur unexpectedly, this contains uncertainty about what will happen, therefore good risk control is needed from the parties involved. To find, analyze, and assess the risk variables that exist in the project location, research is needed. Identifying, assessing, and analyzing hazards will be used to conduct this research using the House Of Risk method. HOR itself is a type of risk management that is obtained from the needs of risk management itself which focuses on preventive actions and then determines the type of risk that is a priority which will then be given mitigation or countermeasures for this risk. Risk can be controlled by implementing risk management including risk identification, risk analysis and risk mitigation. Identification is the initial stage in risk management, further investigation is carried out which is called risk analysis. The last implementation of risk management is by taking action to deal with the occurrence of the risks that have been analyzed. It can be concluded that risk management is an effort made to avoid, prevent the bad consequences that may occurance.